Pedagogical Foundations for Integrating Traditional Folk Games into Modern Primary Education Curriculum - Muazzamkhon Shamuratova (International Journal on Integrated Education, 2026)
Game-based learning has emerged as a significant pedagogical approach in contemporary education systems due to its capacity to enhance cognitive engagement, motivation, and meaningful learning experiences. At the same time, traditional folk games represent a valuable cultural resource that has remained underutilized within formal school curricula. This study examines the pedagogical foundations for integrating traditional folk games into modern primary education programs and evaluates their impact on pupils’ intellectual development and learning engagement. A quasi-experimental research design was employed involving primary school students divided into experimental and control groups. The experimental group participated in structured learning activities incorporating traditional folk games aligned with curriculum objectives, while the control group followed conventional instructional methods. Data were collected through classroom observations, cognitive development tests, and student engagement questionnaires. Quantitative and qualitative analyses demonstrated significant improvements in attention, memory performance, problem-solving ability, and collaborative learning behavior among students exposed to folk game–based instruction. Findings indicate that culturally grounded play activities support active learning environments, strengthen socio-cognitive skills, and foster deeper conceptual understanding. The study contributes to international pedagogical discourse by proposing a structured integration model linking cultural heritage with competency-based education frameworks. Results highlight the importance of culturally responsive pedagogy and provide practical strategies for educators seeking innovative instructional approaches. The research confirms that integrating traditional games into modern curricula promotes holistic child development while preserving cultural identity within globalized educational contexts.